Analytical Study Of Performance Efficiency and Organizational Commitment of Iraqi Central Federation Athletics' Referees - Shihab, Zahraa; Ismael, Humam (Journal of Physical Education, 2019)
The success of Championships depend on the proficiency of the personal the organize and administrate these championships. The aim of the research is to identify the reality of performance proficiency and commitment of referees in the central federation for athletics. The researchers applied the performance proficiency scale and the descriptive method on (40) referees. The data was collected and treated using SPSS to conclude that referees of Iraqi central federation for athletics have high level of performance proficiency and organizational commitment ability. Finally the researchers recommended using the scale for measuring referees of Iraqi central federation for athletics.